SCIENTIFIC EXPLANATIONS AND PIAGETIAN OPERATIONAL LEVELS. - Bass, Joel E.; Maddux, Cleborne D. (Journal of Research in Science Teaching, 1982)
The article presents a study that examined the problems of students in learning and remembering the explanations presented in physical science courses. To test the problems, investigations were made on the effect of levels of operational thought on the explanations which ninth grade and college physical science students reconstructed after an instruction. The students were classified through Piagetian tests as concrete or formal operational. Results showed that both concrete and formal subjects were successful in recalling explanations requiring the chaining of two implication statements. In teaching causal explanation, teachers were advised to furnish some external structuring which students can rely on in relating the several propositions of the explanations.